Writing shame : contemporary literature, gender, and negative affect - Mitchell, Kaye (Edinburgh University Press, 2020)
Through readings of an array of recent texts - literary and popular, fictional and autofictional, realist and experimental - this book maps out a contemporary, Western, shame culture